The examination of the personality traits and optimal performance mood of the university athletes - A. Ceviker; K. Ozlu; G. Deryahanoglu; C. Demirdoken; H. Turkay (IP Iermakov S.S., 2020)
Background and Study Aim: The aim of this study is to investigate the relationship between personality traits and optimal performance mood in response to gender, sports branch, weekly training hours of the athletes competing in the university league variables. Material and Methods: A total of 250 volunteer athletes from 17 universities, 75 female and 175 male, participated in the study. 95 of the athletes are basketball and 155 are volleyball players. In addition to the personal information form which includes demographic information prepared by the researchers, "Optimal Performance Mood Scale" developed by Jackson and Eklund (2004) and adapted to Turkish by Aşçı et al. (2007) and "5-factor personality traits scale" developed by Benet-Martinez, John (1998) and adapted to Turkish by Schmitt, Allik, McCrae and Benet-Martinez (2007) were applied to the participants. Frequency analysis was applied in order to determine the participants' demographic information based on the statistical data analysis, and unpaired t-test was applied to determine the personal traits and optimal performance mood scores in response to gender, branch, weekly training sessions. Furthermore, in order to determine the relationship between that personal traits and optimal performance moods correlation test was applied. Statistical significance level was accepted as p <0.05. Results: As a result of the analysis of the data obtained; while there was no significant difference between the athletes according to the gender variable, it was concluded that there was a significant difference between sports branch, weekly sport variables and personality traits and optimal performance moods. In addition, a positive correlation was found between the participants' personality traits and optimal performance moods as a result of the correlation test (r=0,608). Conclusions: This study has proved that personality traits and optimal performance moods effect one another positively and gender variable makes no significant difference. Yet, sport branches and weekly training hours makes meaningful differences between general and subscales scores.